Analisis Teknikal dan Fundamental Saham Pada Indeks Sharia Growth dengan Metode Peramalan Deterministik dan Error Correction Model (ECM) - Nurfajriyani; Elsa Amelia Nur Arimba; Nisrina Aulia Salsabila; Ratna Maulidah Wulandari; Muhammad Hasan Alwi Abu Sifa; Naswa Sahira; Muhammad Akmal Hafiz Abidin; Bintang Amirul Mukminin; Fausania Hibatullah; Bambang Hadi Santoso Dwidjosumarno (CV. Creative Tugu Pena, 2024)
Stock investment is a form of long-term capital allocation aimed at generating future returns while supporting economic growth through funding innovation and production capacity. This study focuses on issuers listed in the Sharia Growth Index, analyzed using a comprehensive approach that includes financial ratio calculations to evaluate fundamental performance, clustering to group stocks based on specific characteristics, and risk-return analysis to assess investment potential and risks. The analysis identified PT Adaro Energy Indonesia Tbk (ADRO) as the selected issuer due to its high returns and strategic role in the mining sector. Subsequently, forecasting methods, including the Error Correction Model (ECM) and Winter’s model, were applied to predict ADRO's stock price movements. The findings indicate that Winter’s model provides the best forecasting results for ADRO, offering high accuracy in predicting future stock price trends. These results provide strategic insights for capital market participants to make more effective and profitable investment decisions. This research serves as a reference for investors in optimizing investment strategies based on integrated technical and fundamental analysis.